Greenland Sea Studies. - Aagaard,Knut (1974)
This report is in three parts. Part I is a short paper co-authored with Clark Darnall and Paul Greisman, summarizing the mooring and current measurements in the Greenland-Spitsbergen Passage. Part II is a paper on the Arctic heat and mass budgets, co-authored with Paul Greisman and based on large part on the 1971-72 current measurements. Part III presents the current measurements themselves. Also includes Rept. nos. Contrib-711 and Contrib-855.